OPTIMALISASI PROGRAM MBKM MAGANG KEPENDIDIKAN TERHADAP KESIAPAN MAHASISWA PRODI PGSD STKIP MELAWI DALAM PRAKTIK MENGAJAR - Joni Albar; Deki Wibowo; Eliana Yunitha Seran (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
The formation of a learning experience is a provision to become a professional teaching candidate. The purpose of this study is to discriminate between student preparation and student stabilization in the Elementary School Teacher Education Study Program (PGSD) in implementing the MBKM Intern Education Program to maximize student experience strengthening programs. This research is descriptive qualitative. Subjects of this study were students of the STKIP Melawi PGSD Study Program, MBKM Educational Internship Participants. This research instrument uses Interview Sheets and Questionnaire Sheets. Data Analysis Using Data Triangulation. The results of the study show that the MBKM Internship Education program has a significant impact by optimizing several preparations that must be carried out. the results of the interviews show that the internship program can foster students' ability to train professionalism in teaching practice. This was corroborated by the results of the questionnaire showing the satisfaction and implementation of the MBKM educational internship program by students participating in educational internships. The conclusion is that strengthening teaching practice safeguards by training professionals in teaching helps in the readiness and stabilization of teaching in the classroom through the Optimization of the MBKM Educational Internship Program.